Análise de coeficientes em fórmulas empíricas de perda de carga contínua em tubos de PVC - Silva, Juciano Gabriel da (2021)
The continuous pressure drop in the pressurized irrigation system is an extremely important factor that must be taken into account when designing hydraulics. For your estimation to be performed correctly, you need precise information about the system, and the choice of suitable equations by the designer. Therefore, the present work has the objectives of: comparing estimates of the head loss by the Darcy-Weisbach equation with the roughness obtained by the Ra parameter of the roughness profile, with the head loss determined in a U-shaped column mercury manometer; develop equations that estimate the head loss coefficients of the Hazen-Williams equations (coefficient C), Scobey (coefficient Ks), Flamant (coefficient b) and Manning (coefficient n). For this purpose, measurements of the Ra parameter of the roughness profile were carried out with the aid of a bench rugosimeter, brand Mitutoyo, model SJ- 410, in PVC tubes, in the transverse and longitudinal direction of the flow. To analyze the performance in the use of the Ra parameter of the roughness profile in determining the distributed head loss and the accuracy of the results obtained by the empirical formulas, the results were submitted to statistical evaluations of agreement indices "d", correlation coefficient "r” and performance “c”, in addition to the estimate of the percentage error. The results estimated by the empirical equations with the coefficients obtained in this study, reduced the percentage error in the determination of head loss when compared to the use of a fixed coefficient for the same manufacturing material of the pipes, in addition to presenting an excellent correlation with results estimated by the equation by Darcy-Weisbach. The roughness values obtained from the Ra parameter of the roughness profile, showed a good correlation with the pressure drop measured in the laboratory and its results ranged from 0.77 to 3.59 μm in PVC tubes with nominal diameters of 32, 40, 50 and 75.